Pengaruh Pemberian Silase Komplit Berbasis Sorgum Clitoria Hasil Integrasi Tanam Campuran yang Berbeda terhadap Profil Darah Kambing Lokal Betina - Diaz, Bartholomeus; Abdullah, Muhammad S.; Maranatha, Grace (Animal Agricultura, 2024)
This study aims to determine the effect of giving complete silage based on sorghum clitoria from the integration of different mixed plantings on the blood profile of hematocrit, erythrocytes and leukocytes of local female goats. The livestock used in this study amounted to 4 female bean goats aged 6-8 months in the range of 17-23 kg with an average of 19.9 kg and a coefficient of variation of 12.0%. This study used the Latin square design method (RBSL) with 4 treatments and 4 periods as a repeat The treatment is R0 = complete feed silage of sorghum, R1 = complete feed silage of sorghum + legume clitoria + bitter melon horti R2 = complete feed silage of sorghum + clitoria legume + cucumber horti, R3 = complete feed silage of sorghum + clitoria legume + long bean horti. The parameters observed are hematrocytes, erythrocytes, leukocytes . The data obtained were analyzed using Fingerprint analysis. Based on the results of the study, the average Hematocrit R0: 31.65; R1: 31.77; R2: 31.46; R3: 31.07; mean Erythrocytes R0: 9.77; R1: 9.78; R2: 9.72; R3: 9.68; mean Leukocytes R0: 10.06; R1: 10.11; R2: 10.12; R3: 10.09; that the administration of sorghum-based complete feed silage as an absorbant has no real effect (P >0.05) on hematocrit, erythrocytes and leukocytes. Thus, it can be concluded that the provision of complete silage based on sorghum clitoria resulting from the integration of different mixed plantings has the same effect and is under normal conditions.